VIRULANCE FACTOR OF Staphylococcus sp. ISOLATED FROM SUBCLINICAL MASTITIS IN ETTAWA GRADE GOAT’S MILK IN SLEMAN REGENCY -YOGYAKARTA - Suwito, W.; Nugroho, W.S.; Wahyuni, A.E.T.H.; Sumiarto, B. (Diponegoro University, 2014)
Stapphylococcus sp., is bacteria that caused subclinical mastitis in Ettawa Grade (EG) goat. Thepurpose of this study was to determine virulance factor Stapphylococcus sp., which was isolated fromsubclinical mastitis EG goat’s milk in Sleman regency, Yogyakarta. A total of 7 isolate Stapphylococcussp., were isolated from subclinical mastitis EG goat’s milk were determinated by several virulancefactors such as haemolysin, clumping factor, and coagulase. Haemolysin was determinated by culture inblood agar plate and incubated in the temperature of 37°C for 24 hours. Clumping factor wasdeterminated by mixing the rabbit plasma with Stapphylococcus sp., in the glass objects. Coagulase wasdeterminated by mixing the rabbit plasma and broth culture of Stapphylococcus sp. After incubated inthe temperature of 37°C for 24 hours in tube, then the gel formation was observed. Haemolytic type ßwas yielded from 5 isolate Stapphylococcus sp., whereas 2 isolates were not haemolytic. Clumpingfactor and coagulase were produced from 2 isolate Stapphylococcus sp. This study showed that not all ofStapphylococcus sp., isolate causing subclinical mastitis in EG goat have virulance factor.